2007
DOI: 10.4049/jimmunol.178.4.2352
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Spontaneous Autoimmunity Driven by 129-Derived Chromosome 1 Loci When Expressed on C57BL/6 Mice

Abstract: Extensive evidence indicates that genetic predisposition is a central element in susceptibility to systemic lupus erythematosus both in humans and animals. We have previously shown that a congenic line carrying a 129-derived chromosome 1 interval on the C57BL/6 background developed humoral autoimmunity. To further dissect the contribution to autoimmunity of this 129 interval, we have created six subcongenic strains carrying fractions of the original 129 region and analyzed their serological and cellular phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
76
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 60 publications
11
76
0
Order By: Relevance
“…Because the vast majority of strains that carry the Sle1b susceptibility alleles are not autoimmune (7), it seems likely that these alleles must interact with polymorphic genes of the normal B6 genome to break tolerance to chromatin. This notion is supported by the finding that, unlike nonautoimmune 129 mice, B6 mice congenic for a 129-derived interval on distal chromosome 1 (denoted 129chr1b) encompassing the Sle1b locus also produce ANA (43). Hence, the genetic backgrounds of BALB.B and C3.SW mice may not be compatible with a role for Sle1 alleles in the ANA responses of these mice.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Because the vast majority of strains that carry the Sle1b susceptibility alleles are not autoimmune (7), it seems likely that these alleles must interact with polymorphic genes of the normal B6 genome to break tolerance to chromatin. This notion is supported by the finding that, unlike nonautoimmune 129 mice, B6 mice congenic for a 129-derived interval on distal chromosome 1 (denoted 129chr1b) encompassing the Sle1b locus also produce ANA (43). Hence, the genetic backgrounds of BALB.B and C3.SW mice may not be compatible with a role for Sle1 alleles in the ANA responses of these mice.…”
Section: Discussionsupporting
confidence: 43%
“…The image was taken at ϫ400 total magnification. genome mediates autoimmunity to chromatin in B6 mice despite carrying a normal Fc␥r2 gene (43,46) (45).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this hypothesis, the increase of primary IgM responses to T-dependent and T-independent Ags, observed in Fc␥RIIB-deficient mice, suggests that Fc␥RIIB can control the activation of naive B cells (24,43,44). Interestingly, Fc␥RIIB-deficient mice develop an autoimmune syndrome (45), although it was later shown that mice from a congenic line carrying a 129-derived chromosome 1 interval on a C57BL/6 background also develop humoral autoimmunity, suggesting that the lack of Fc␥RIIB expression is not the only parameter responsible for the autoimmune phenotype (46). However, overexpression of Fc␥RIIB, independent from this 129 region, suppresses the autoimmune syndrome, an observation that excludes a relationship between the autoimmune syndrome and the adjacent area of 129 DNA (47).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is elevated in serum and BAL of C57.SHIP-1 2/2 mice (6,8,10,31). It is well known to influence hematopoietic progenitor number and myelopoiesis: injection of IL-6 into mice can induce myelopoiesis and myeloproliferative disease (32), and IL-6 can synergize with other cytokines to drive production of immature hematopoietic progenitors (33,34 (20,(37)(38)(39)(40)(41)(42), and there is evidence that the 129 strain is autoimmune prone (43,44). SHIP-1 2/2 mice share many phenotypes with FcgRIIB 2/2 mice, in keeping with a major role for SHIP-1 immediately downstream of this receptor (45).…”
Section: Discussionmentioning
confidence: 99%